2022
DOI: 10.1108/scm-05-2021-0235
|View full text |Cite
|
Sign up to set email alerts
|

The impact of supply chain quality leadership on supply chain quality integration and quality performance

Abstract: Purpose As quality issues become more prominent in supply chain (SC) management, understanding the factors driving SC quality integration (SCIQ) and quality performance has become increasingly important, shifting the focus of quality management to firms in SCs. This study aims to examine the role of SC quality leadership (SCQL) in facilitating SCIQ and its direct and indirect relationship with quality performance. Design/methodology/approach Data on 400 Chinese manufacturing firms were collected using survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 99 publications
0
9
0
Order By: Relevance
“…(2020) for undergraduate students of Ireland and Spain. The SC users can benefit from this methodology application in reducing the time to find the professionals with the necessary skills and in avoiding high expenses in the reskilling and upskilling current employees, factors identified by studies focused on the changes in the SC talent and labour on the rise (Luo et al. , 2022; Michel, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…(2020) for undergraduate students of Ireland and Spain. The SC users can benefit from this methodology application in reducing the time to find the professionals with the necessary skills and in avoiding high expenses in the reskilling and upskilling current employees, factors identified by studies focused on the changes in the SC talent and labour on the rise (Luo et al. , 2022; Michel, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Results from the case study have significant importance in the process of fulfilling the SC talent demand in Brazil; thus, the proposed methodology can help SC educators in developing EMs in order to act anticipatory rather than reactive to the industry's skillsets requirements, a finding similar to the results obtained by Wagner et al (2020) for undergraduate students of Ireland and Spain. The SC users can benefit from this methodology application in reducing the time to find the professionals with the necessary skills and in avoiding high expenses in the reskilling and upskilling current employees, factors identified by studies focused on the changes in the SC talent and labour on the rise (Luo et al, 2022;Michel, 2022). Regarding the SC's interest, the talent with necessary skill may increase visibility in ongoing and upcoming disruptions, a finding that echoes most of the literature, regardless of the country, sector and size of the companies analysed by Thorn (2021).…”
Section: Assessing Supply Chain Educational Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…improper storage or handling) (Bode and Wagner, 2015; Giunipero and Aly Eltantawy, 2004). Global sourcing also presents challenges associated with maintaining consistency of product quality (Luo et al , 2023) and makes firms more susceptible to product recalls (Bruccoleri et al , 2019). In response to these challenges, previous research has found that firms operating global supply chains, compared to firms operating domestic supply chains, were more likely to invest in education programs for suppliers and customers to protect against problems associated with product safety and supply chain security (Whipple et al , 2009).…”
Section: Literature Reviewmentioning
confidence: 99%